2016
DOI: 10.1007/s12034-016-1263-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spin polarization on the structural properties and bond hardness of Fe x B (x = 1, 2, 3) compounds first-principles study

Abstract: In this paper, spin and non-spin polarization (SP, NSP) are performed to study structural properties and bond hardness of Fe x B (x = 1, 2, 3) compounds using density functional theory (DFT) within generalized gradient approximation (GGA) to evaluate the effect of spin polarization on these properties. The non-spin-polarization results show that the non-magnetic state (NM) is less stable thermodynamically for Fe x B compounds than spinpolarization by the calculated cohesive energy and formation enthalpy. Spin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Fortunately, in recent years theoretical study has been become an effective method to explore its properties. In particular, the structure, stability, elastic properties, hardness, magnetism and electronic structure of Fe 2 B in different conditions (e.g., pressure) have been extensively investigated [32][33][34][35][36][37][38][39][40]. Additionally, Anand Kumar et al [32] reported the structural transformation and low temperature transport properties of Fe 2 B under high pressure.…”
mentioning
confidence: 99%
“…Fortunately, in recent years theoretical study has been become an effective method to explore its properties. In particular, the structure, stability, elastic properties, hardness, magnetism and electronic structure of Fe 2 B in different conditions (e.g., pressure) have been extensively investigated [32][33][34][35][36][37][38][39][40]. Additionally, Anand Kumar et al [32] reported the structural transformation and low temperature transport properties of Fe 2 B under high pressure.…”
mentioning
confidence: 99%